Micropatterned viral membrane clusters for antiviral drug evaluation - Park, Soohyun (2021)
The function of biological nanoparticles, such as membrane-enveloped viral particles, is often enhanced when the particles form higher-order supramolecular assemblies. While there is intense interest in developing biomimetic platforms that recapitulate these collective properties, existing platforms are limited to mimicking individual virus particles. Here, we present a micropatterning strategy to print linker molecules selectively onto bioinert surfaces, thereby enabling controlled tethering of biomimetic viral particle clusters across defined geometric patterns. By controlling the linker concentration, it is possible to tune the density of tethered particles within clusters while enhancing the signal intensity of encapsulated fluorescent markers. Time-resolved tracking of pore formation and membrane lysis revealed that an antiviral peptide can disturb clusters of the membrane-enclosed particles akin to the targeting of individual viral particles. This platform is broadly useful for evaluating the performance of membrane-active antiviral drug candidates, whereas the micropatterning strategy can be applied to a wide range of biological nanoparticles and other macromolecular entities.